Design Development of Arabic-Rumi Transliteration Module With Virtual Reality Concept to Improve Primary School Students’ Arabic Reading Skills : Design and Development - Ahmat Syafri, Norazman; Ramli, Saipolbarin (Multidisciplinary Applied Research and Innovation, 2025)
This paper presents the design and development of an Arabic-Rumi Transliteration Module integrated with a Virtual Reality (VR) concept aimed at improving Arabic reading skills among primary school students. The background of the study highlights the challenges faced by students in mastering Arabic script due to the differences in script and phonetics compared to their native language. The primary objective of this research is to create an engaging and interactive learning module that bridges this gap and enhances the learning experience.The development process involves a meticulous design phase, where educational theories and VR technology are integrated to create a user-friendly module. The transliteration module is designed to assist students in recognizing Arabic letters and their corresponding sounds through an immersive VR environment, providing a multi-sensory learning experience. A mixed-method approach is employed to evaluate the effectiveness of the module. Quantitative data is collected through pre- and post-tests to measure improvements in reading skills, while qualitative data is gathered from student feedback and observations to understand their learning experiences.The results demonstrate significant improvement in students’ ability to read Arabic text accurately and confidently. The VR environment proved to be highly engaging, keeping students motivated and enhancing their retention of the material. This study concludes that the integration of VR in language learning modules can be a powerful tool in overcoming language barriers and improving reading skills among primary school students.